429 Incidence and management of adverse events among COVID-19 vaccination receipts with Brugada syndrome. Results from a multicentre-prospective European registry. (8th December 2021) - Cetera, Rosa; Santoro, Francesco; Gianfrancesco, Domenico; D'Arienzo, Girolamo; Bartolomucci, Francesco; Pellegrino, Pierluigi; Brunetti, Natale Daniele
Abstract: Aims: Patients with Brugada syndrome have an increased risk of life-threatening arrhythmias when experience fever. Therefore, a prompt treatment of non-steroidal anti-inflammatory drugs (NSAI) is suggested in these patients. COVID-19 vaccination can be associated with fever in about 20% of patients. The aim of the study is to evaluate the incidence and management of adverse events within 48 h from COVID-19 vaccination among Brugada patients. Methods and results: Eighty patients were enrolled from a prospective registry involving four European hospitals with a dedicated inherited disease ambulatory. Cardiological follow-up was performed within one month from vaccination. Mean age was 47 ± 17 years, 80% (num = 63) were male. Prevalence of Brugada types 1, 2, and 3 was as follows: 25% type 1, 39% type 2, and 24% type 3. Twenty-six percent of patients had an implantable cardioverter defibrillator (ICD). Within in 48 h from vaccination, 35% (num = 28) of patients experienced joint paint, 19% (num = 15) fever and 4% (num = 3) chest pain. In 8 out of 15 fever episodes body temperature was ≥38 degrees and treated with NSAI drugs. No patients had syncope or fatigue episodes and no arrhythmic episodes were recorded in patients with ICD. Conclusions About 20% of patients experienced fever after Covid-19 vaccination but no patient experienced life-threatening arrhythmias. Careful evaluation of body temperature and administration of NSAI in case of temperature higher than 38 is suggested.